London's number one dog-walking agency - MacDougall, Kate (William Morrow, an imprint of HarperCollinsPublishers, 2021)
"The irresistibly charming memoir of a young woman who started her own business as a dog walker for London's busy, well-heeled dog lovers. A true love letter to London, dogs, and growing up"--